Application of the Box–Behnken Design in the Development of Amorphous PVP K30–Phosphatidylcholine Dispersions for the Co-Delivery of Curcumin and Hesperetin Prepared by Hot-Melt Extrusion - Kamil Wdowiak; Lidia Tajber; Andrzej Miklaszewski; Judyta Cielecka-Piontek (Pharmaceutics)
Background: Curcumin and hesperetin are plant polyphenols known for their poor solubility. To address this limitation, we prepared amorphous PVP K30–phosphatidylcholine dispersions via hot-melt extrusion. Methods: This study aimed to evaluate the effects of the amounts of active ingredients and phosphatidylcholine, as well as the process temperature, on the performance of the dispersions. A Box–Behnken design was employed to assess these factors. Solid-state characterization and biopharmaceutical studies were then conducted. X-ray powder diffraction (XRPD) was used to confirm the amorphous nature of the dispersions, while differential scanning calorimetry (DSC) provided insight into the miscibility of the systems. Fourier-transform infrared spectroscopy (FTIR) was employed to assess the intermolecular interactions. The apparent solubility and dissolution profiles of the systems were studied in phosphate buffer at pH 6.8. In vitro permeability across the gastrointestinal tract and blood–brain barrier was evaluated using the parallel artificial membrane permeability assay. Results: The quantities of polyphenols and phospholipids were identified as significant factors influencing the biopharmaceutical performance of the systems. Solid-state analysis confirmed the formation of amorphous dispersions and the development of interactions among components. Notably, a significant improvement in solubility was observed, with formulations exhibiting distinct release patterns for the active compounds. Furthermore, the in vitro permeability through the gastrointestinal tract and blood–brain barrier was enhanced. Conclusions: The findings suggest that amorphous PVP K30–phosphatidylcholine dispersions have the potential to improve the biopharmaceutical properties of curcumin and hesperetin.